2014
DOI: 10.1021/bc5003289
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Imaging of Intraperitoneally Disseminated Tumors in Model Mice by Using Activatable Fluorescent Small-Molecular Probes for Activity of Cathepsins

Abstract: It is difficult to completely remove carcinomas in unguided ablative surgery because they cannot be distinguished with the unaided human eye. Therefore, in order to precisely visualize tiny tumors and the borders between cancerous lesions and normal tissues, we have been developing fluorescence probes activatable only in cancer cells. We previously reported the hydroxymethylrhodamine green (HMRG)-based fluorescence probe gGlu-HMRG for γ-glutamyltransferase (GGT), which is overexpressed in a variety of cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 49 publications
0
39
0
Order By: Relevance
“…Therefore, cathepsin B-specific imaging probes and pro-drugs have received much attention for the development of new theranostic platforms for cancer therapy. [14] Thec athepsin Bspecific peptide caged metabolic precursor consists of three major components,acathepsin B-specific cleavable peptide moiety (Lys-Gly-Arg-Arg,K GRR), as pacer linker of paminobenzyloxycarbonyl (S), and the metabolic precursor of triacetylated N-azidoacetyl-d-mannosamine (Ac 3 ManNAz), resulting in RR-S-Ac 3 ManNAz (Scheme 1a). We have confirmed that the cathepsin Bs pecifically cleavable peptide moiety of Lys-Gly-Arg-Arg (KGRR) was successfully cleaved by the targeting cathepsin Be nzyme using in vitro enzyme tests and in vivo tumor-bearing mice.…”
Section: Metabolicglycoengineeringisausefulbiologicaltechniquementioning
confidence: 99%
“…Therefore, cathepsin B-specific imaging probes and pro-drugs have received much attention for the development of new theranostic platforms for cancer therapy. [14] Thec athepsin Bspecific peptide caged metabolic precursor consists of three major components,acathepsin B-specific cleavable peptide moiety (Lys-Gly-Arg-Arg,K GRR), as pacer linker of paminobenzyloxycarbonyl (S), and the metabolic precursor of triacetylated N-azidoacetyl-d-mannosamine (Ac 3 ManNAz), resulting in RR-S-Ac 3 ManNAz (Scheme 1a). We have confirmed that the cathepsin Bs pecifically cleavable peptide moiety of Lys-Gly-Arg-Arg (KGRR) was successfully cleaved by the targeting cathepsin Be nzyme using in vitro enzyme tests and in vivo tumor-bearing mice.…”
Section: Metabolicglycoengineeringisausefulbiologicaltechniquementioning
confidence: 99%
“…In this respect, a new method reported by Urano et al which allowed rational development of intramolecularly caged fluorescence probes that were designed to be activated only when specific peptidases expressed on cancer cells were detected [50], could advance usefulness of theranostic agents. If more cancer-specific enzymes are discovered [51], their strategy may serve as an attractive foundation for increasing the variety of small-molecule-based theranostic agents, owning to its flexibility against different enzymes, multiple potential caging sites for forming an AND gate, and easy convertibility to a photosensitizer [52]. Additionally, the discovery of enzymes that can cleave specific molecular bonds that are specific biomarkers of other diseases would also expand the availability of small-molecule-based theranostic agents.…”
Section: Comparison Of Each Modality and Discussion Of Future Prospectsmentioning
confidence: 99%
“…Urano et al have functionalized this fluorophore with various substrate moieties to produce a fluorescent signal when removed by a target enzyme. Targets include leucine aminopeptidase (Leu-HMRG) (Sakabe, et al, 2013), fibroblast activation protein (Ac-GlyPro-HMRG) (Sakabe, et al, 2013), β-galactosidase (βGal-HMRG) (Kamiya, et al, 2011), γ-glutamyltransferase (gGlu-HMRG) (Urano, et al, 2011), and most recently cathepsins (ZFR-HMRG) (Figure 4E) (Fujii, et al, 2014). This type of turn-on dye has great promise, as it is relatively small and does not require additional large quencher groups.…”
Section: Substrate and Activity-based Probesmentioning
confidence: 99%